INTEGRATING ENVIRONMENTAL LITERACY INTO INDONESIAN LANGUAGE LEARNING MATERIALS: A STRUCTURED DESIGN SYNTHESIS FOR SUSTAINABLE LITERACY PEDAGOGY - Siti Mayang Sari; Zikrul Rizki; Carlo Antonio Garcia (SENSEI RESEARCH CENTER, 2025)
The environmental problem in Indonesia is getting worse, so the students must be taught about the environment from an early age. Actually this can be integrated into Indonesian language learning because language learning uses texts and the texts can be about the environment. This article discusses the integration of environmental literacy into Indonesian language learning materials. The method used is literature study. The result shows that environmental literacy can be integrated through the selection of texts, the design of tasks, and also the assessment. It is suggested that the writers of teaching materials pay attention to environmental literacy so that the students not only can use the language but also care about the environment.